Pengaruh Personal Values Terhadap Persepsi Dalam Penghematan Energi di Kantor - Alfikhairina Jamil; Ulfa Mazaya (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Energy conservation remains a challenging practice to implement in office. Several factors hinder energy-saving behaviors in the office, including physical factors such as the numerous electronic devices that heavily rely on electricity, the need for lighting to illuminate workspaces, thermal comfort dependent on air conditioning, and security as well as safety measures often supported by the use of 24-hour surveillance cameras. Additionally, habitual or ingrained behaviors also pose barriers to energy conservation efforts. This study aims to explore employees' perceptions of the importance of energy conservation in the office.